DESIGN OF A 20-STORY "PACIFIC TOWER" HIGH-RISE RESIDENTIAL BUILDING IN LOS ANGELES, CALIFORNIA, USA - Khoschanova, Kamila; Abdildayeva, Nurdina; Yembergenova, Akmaral; Aman, Samir; Kuan, Yerassyl; Yerzhanuly, Islam (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This paper proposes designing and constructing a 20-story residential building at 1201 South Grand Avenue in Los Angeles, California, in a densely populated commercial district. The growing population in Los Angeles has spurred a demand for innovative residential construction solutions, prompting a comprehensive approach that considers architectural, structural, material, and geotechnical factors. The proposed building has 19 residential floors and 1 commercial floor with a gross area of 1138. 3 𝑚 . All of the architectural, structural, and geotechnical design procedures were done in accordance with IBC, ASCE, LA Building Code guidelines. The site is located in a seismically active region, which was taken into consideration during the design of foundation and structural members. The geotechnical design included site response analysis to investigate soil behavior under strong earthquake ground motions. Additionally, detailed foundation design and retaining wall design was provided. Lastly, project costs, risks, and schedules were estimated and the project deadline to put into operation is set to 2026.
Keywords: Type of access: Restricted; Structural Design; Civil Engineering; Residential Building; Seismic Area; Architectural Design; Geotechnical Design